A Primer for Design and Systems Thinkers: A First-Year Engineering Course for Mindset Development - Jac Ka Lok Leung; Davy Tsz Kit Ng; Chi-Ying Tsui (MDPI AG, 2024)
Teaching students to think in complex systems and design is presumably intricate, creative, and nonlinear. However, due to the overwhelming number of standardized tools and frameworks, the process sometimes ends up being procedural and deductive. Conformity to rigid procedures loses the intention of creative problem-solving towards tackling wicked problems. This paper proposes a project-based approach to instill the mindsets for those who aspire to be design and systems thinkers through a first-year engineering course. Using the ADDIE model, the instructional design was implemented in three modules focusing on design, systems, and integration for real-world applications. The instructional design was evaluated via course feedback surveys and focus-group interviews. Students indicated positive impacts on creative mindsets, habits of systems thinkers, and interdisciplinary awareness. However, negative comments about the course arrangement such as heavy workload and disconnection between topics were identified. Suggestions from students, challenges faced by the instructors, and recommended practices are discussed. In times of increasing need to reform higher education due to digitization and artificial intelligence, this study provides a timely investigation of a new project-based and mindset-focused pedagogy in design and systems thinking education.